2014
DOI: 10.3109/09638237.2014.928403
|View full text |Cite
|
Sign up to set email alerts
|

Automated telehealth for managing psychiatric instability in people with serious mental illness

Abstract: Background Serious mental illness (SMI) with psychiatric instability accounts for disproportionately high use of emergency room visits and hospitalizations. Aim To evaluate the effectiveness of an automated telehealth intervention supported by nurse health care management for improving psychiatric illness management and reducing acute service use among individuals with SMI and psychiatric instability. Methods Thirty-eight individuals with SMI received the automated telehealth intervention for 6 months. Psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…Most studies were designed to assess feasibility and were single-arm pilot studies, 9 18 27 28 43 47 49 51 52 54–62 66 67 69 70–74 or observational studies. 21 29–31 64 68 Some were randomised controlled trials (RCTs) 19 20 22 25 26 44 45 50 59 63 65 and some were non-randomised trials 46 53 that reported the efficacy of technology-based symptom monitoring in terms of reduced severity of symptoms, 19 22 25 26 remission rates 44 or increased adherence compared with paper monitoring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies were designed to assess feasibility and were single-arm pilot studies, 9 18 27 28 43 47 49 51 52 54–62 66 67 69 70–74 or observational studies. 21 29–31 64 68 Some were randomised controlled trials (RCTs) 19 20 22 25 26 44 45 50 59 63 65 and some were non-randomised trials 46 53 that reported the efficacy of technology-based symptom monitoring in terms of reduced severity of symptoms, 19 22 25 26 remission rates 44 or increased adherence compared with paper monitoring.…”
Section: Resultsmentioning
confidence: 99%
“… 65 In other studies, monitoring was a component of an intervention, which when evaluated, reported positive impact on symptoms, 20 45 59 63 mixed findings 46 53 or non-significant findings. 50 Five papers contained <10 participants, 52 58 64 67 74 21 papers contained <50 participants, 9 18 22 43 46–49 53–57 60 65 66 69–73 16 papers contained between 50 and 99 participants, 1 20 21 25 26 29–31 44 45 50 51 59 61–63 and five papers contained 100 or more participants, 19 27 28 68 one of which was the longitudinal ongoing study of ChronoRecord. 32–42 …”
Section: Resultsmentioning
confidence: 99%
“…However, concerning case studies, all conducted evaluation at the end of the intervention. Although several aspects of evaluation have been found in conceptual articles [32][33][34][35][36][37][38][39]41], the case studies mostly evaluated clinical [20,[42][43][44][46][47][48][49][52][53]55,[59][60][61][64][65], and human/social aspects [42,[46][47][48][49][53][54][55]59,61,63,65].…”
Section: Discussionmentioning
confidence: 99%
“…This requires specific skills in the coach as well as close monitoring. One recent study reports on the effects of providing expert support through a trained telehealth nurse who viewed the output from an adapted version of Health Buddy (Pratt et al, 2015 ). The nurse examined the information collected from each participant several times each day during the working week and followed a communication protocol depending on the category of response from the participant (red, yellow and green) where red are responses that are of major concern.…”
Section: Reciprocitymentioning
confidence: 99%